Comparative Evaluation of Novel Configurations under Shading Conditions - Sharma S.; Varshney L.; Saket R.K. (My University, 2025)
The main aim of this paper is to make a comparative analysis of Total Cross Tied (TCT), Bridge Link (BL), Honey Comb (HC) and Magic Square (MS) topologies. Due to shading, number of power peaks is obtained in power vs voltage curve which leads in enhancing power losses. For weakening this effect of shading on PV array, reconfiguration technique is adopted named as MS with same electrical connections as of TCT. This relocation of rows and column elements assist in extracting uniform difference in current. Different shading scenarios are considered and applied on each configuration to extract power output. In addition to power output, Fill Factor (FF), losses due to mismatch and efficiency parameters are also calculated for effective analysis. For testing the validity of new technique, four shading patterns are used and performance is evaluated. The results are verified by simulatíon via MATLAB/SIMULINK software. By the results, it is clear that MS is far better among all configurations. © 2022. JES on-line: journal/esrgroups.org/jes. All Rights Reserved.